DEVELOPMENT OF THE “BUKUSAKU PRASIAJA DIGITAL” WORKBOOK ON THE THEME OF NATURE CONSERVATION TO FOSTER CHARACTER DEVELOPMENT AT KEMALA BHAYANGKARI KINDERGARTEN IN PALEMBANG - Kurnia Dewi; Yecha Febrieanitha Putri; Reza Yunita; Diah Ayu Nawangulan (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2026)
investigates the development and improvement of a digital pocketbook focused on environmental conservation themes aimed at promoting character development in early childhood education, specifically at Kemala Bhayangkari Kindergarten, Palembang. This highlight role important family in form character children , with emphasize that communication positive in family is very important For prevent problem like bullying and promoting character like independence and responsibility answer . Findings study show that educators in education child age early childhood (PAUD) feel significant benefits from availability book pocket that can used in a way flexible in various environment . This is in line with study previously underlined the need source Power kind of That in activity extracurricular activities . This article also discusses various method preservation environment that can integrated to in practice education , such as planting trees and management garbage , which functions as lesson practical for children . In addition , research This identify the need various activities For implant values character , especially remember challenges posed by learning distance Far during pandemic , which has an impact bad for development character students . Stage design book this digital pocket involving manufacturing engaging content that is in tune with principles education character , with use tool help like Canva and Flipbook for ensure accessibility and interactivity